From Oral to Archive: Documentation of the Transmigrant Experience of Sungai Bahar, Jambi Province - Mustafa, Hanif Risa; Pradita, Dennys; Lestari, Inda; Pratama, Amor Seta Gilang; Mahanani, Nugrahadi (Proceeding International Conference on Malay Identity, 2024)
This paper examines the process of documenting the experiences and memories of transmigrants in Sungai Bahar. The memories and experiences of the early transmigrants of Sungai Bahar need to be documented as they age and the number of actors decreases. The results of the documentation can be used as historical sources. The documentation is done digitally which can be accessed by all groups. The documentation results show that the transmigrants have their own experiences starting from the registration process, departure to placement in Sungai Bahar. Furthermore, placement in the Bahar River with forest conditions and partly in the form of oil palm plantations is a challenge for migrants in the Bahar River forest. The existence of documentation that can be accessed by all groups can facilitate documentation and disseminate historical sources for academics or history owners or residents.